Tom Kahn papers - Kahn, Tom.
Correspondence, memoranda, speeches and statements, writings, notes, newspaper clippings, printed matter, photographs, and other papers relating to Kahn's activities as a civil rights and labor activist. Documents Kahn's work with Bayard Rustin, particularly in preparation for the March on Washington for Jobs and Freedom in 1963, and with Henry M. Jackson during Jackson's presidential campaign in 1972. Subjects include the civil rights movement, international affairs, national and international labor issues, and social democracy.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Civil rights and labor activist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Jackson, Henry M. -- 1912-1983.; Rustin, Bayard, -- 1912-1987.; Civil rights -- United States; Civil rights demonstrations -- Washington (D.C.); International relations; Labor; Labor -- United States; Labor movement; Labor movement -- United States; Presidents -- United States -- Election -- 1972.; Socialism; United States -- Politics and government -- 1969-1974.; Civil rights activists; Labor activists